Características fitotécnicas e anatômicas de plântulas micropropagadas de Tillandsia bulbosa Hook - Vasconcelos, Márcia Raquel Moura (2016)
Bromeliads are known worldwide for its ornamental potential. In Brazil the species of Tillandsia can be found in the Atlantic Forest, Amazon Forest and rock grassfields. The aim of this study was to investigate the influence of substrate mixtures and fertilization with nitrogen, phosphorus and potassium in micropropagated plantlets of Tillandsia bulbosa, allied with anatomical analyzes of the leaves. The experiments were conducted in the Laboratory of Tissue Culture and Plant Breeding of the Department of Agricultural Engineering (DEA), Federal University of Sergipe (UFS). The first experiment was carried out in a completely randomized design, testing five substrate mixtures, being coconut coir: earthworm castings (2:1); coconut coir: earthworm castings: sand (1:1:1); coconut coir: earthworm castings: sand (2:1:1); coconut coir: earthworm castings: sand (2:2:1); and vermiculite: earthworm castings (2:1). The second experiment was carried out in a completely randomized design, where we used urea, simple superphosphate phosphate and potassium chloride as NPK sources, respectively, testing 50, 100, 200 and 400%, distributed in the following treatments: full application at planting; ½ at planting and ½ at 80 days after planting; ⅓ at planting, ⅓ at 50 days after planting and ⅓ at 100 days after planting; and ¼ at planting, ¼ at 30 days after planting, ¼ at 60 days after planting and ¼ at 120 days after planting. We performed an anatomical study in both acclimatization experiments, and the first leaves were collected in the implementation and every 20 days (0, 20, 40, and 60 days) and in the second experiment, leaves were collected at 180 days. We performed an anatomical study in both acclimatization experiments, and in the first assay leaves were collected at the implantation and at every 20 days (0, 20, 40 and 60 days), and in the second experiment, leaves were collected at 180 days. The results of the first experiment showed that the substrate bulbosa T. responded similarly to the different substrate mixtures used in the acclimatization phase. The results obtained in the first experiment of substrate mixtures showed that T. bulbosa responded similarly to the different tested substrate mixtures, during the acclimatization phase. Plants from 60 days of acclimatization, show anatomical features that can facilitate adaptation to field conditions. Fertilization with 50 and 100% of fertilizer, based on nitrogen, phosphorus and potassium, provided the best results in the development of plantlets when applied at planting, without the need of installment. The increase in fertilizer concentrations influenced the development and thickening of cell leaves.